Ekowisata sebagai Sumber Belajar; Menanamkan Nilai Cinta Lingkungan Melalui Pendidikan Berbasis Alam - Violeta Wiendia Jaya; Muhammad Misbahudholam AR; Lailatul Jannah; Windiani Rofiana (Kampus Akademik Publiser, 2025)
This study aims to explore the role of ecotourism as a learning resource in instilling environmental love values through nature-based education. Using a qualitative approach, this research involves elementary school students participating in ecotourism activities designed to enhance environmental awareness. The findings indicate that student involvement in outdoor activities focused on local ecosystems not only increases their knowledge about the environment but also triggers positive changes in pro-environmental behavior. Additionally, collaboration between schools and local communities provides relevant context for students, strengthening their understanding of local wisdom and sustainable practices. These findings emphasize the importance of integrating ecotourism into the education curriculum as an effective method for instilling environmental love values among the younger generation. This study recommends that schools actively implement ecotourism programs and engage local communities in the educational process to create individuals who are more caring and responsible toward the environment.